Self-Directed Learning Toward Outcome-Based Education (OBE): An Approach to Teaching Pedagogy - Leovigildo Lito Mallillin (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
Modern educational transformation demands a paradigm shift from conventional teaching to more dynamic approaches, where self-directed learning (SDL) and outcome-based education (OBE) serve as crucial elements in fostering student independence and ensuring measurable competency. This study aims to analyze the integration of SDL and OBE as a pedagogical teaching approach. A descriptive quantitative research design was employed, utilizing a purposive sampling technique to select 25 respondents. The results indicate that assessing learning readiness focuses on student-centered outcomes to define OBE expectations, while setting learning goals provides students with independent opportunities, feedback mechanisms, and decision-making skill development. Furthermore, engagement in the learning process emphasizes the interconnection between SDL approaches and instructional goals. Monitoring and evaluation provide a well-articulated roadmap for teaching and learning experiences, while reflection fosters adaptability and lifelong learning approaches necessary for quality education. Structurally, the OBE approach empowers students through personal goal setting, time management, and accountability. In conclusion, the synergy between SDL and OBE effectively empowers students as the center of learning, ensuring the acquisition of intended learning outcomes through a transparent and structured pedagogical framework.